Surgery for Cutaneous Squamous Cell Carcinoma and its Limits in Advanced Disease - David Moreno-Ramírez; Francisca Silva-Clavería; Almudena Fernández-Orland; Noemí Eiris; Andrés Ruiz-; Lara Ferrándiz (Mattioli1885, 2021)
Surgery remains the first-line therapeutic option for most patients with cutaneous squamous cell carcinoma (cSCC). However, in the current therapeutic landscape, surgery must attempt to the complete tumor resection (R0 resection) with the lowest risk of surgical complications. This double aim is usually accomplished through standard excision with clinical margins in patients with low-risk tumors or by some of the micrographically controlled surgery procedures for patients with tumors at high-risk of local recurrence and metastasis. Surgery is also a first-line treatment for nodal metastases of cSCC as well as an option to consider in patients who develop recurrences while receiving immunotherapy, or as a palliation procedure in patients with advanced tumors. Neoadjuvant immunotherapy, that is the use of a medical treatment before surgery, is under investigation in patients with cSCC. The decision-making process and guidelines recommendations regarding cSCC surgery are reviewed in this manuscript.